The identity of some specimens previously (mis)identified as Rhinoleucophenga obesa (Loew) (Diptera: Drosophilidae) in Brazil, based on morphological and molecular data, with implications on distribution - Poppe, Jean Lucas; Gottschalk, Marco Silva; Deprá, Maríndia; Schmitz, Hermes José; Valente, Vera Lúcia Silva (Zootaxa, 2019)
Rhinoleucophenga Hendel is an endemic genus of the New World with most species recorded in Brazil. Rhinoleucophenga obesa (Loew) seemed to be the most widespread species, being recorded in the United States of America, Mexico and Brazil. In the Neotropical region, identifications of R. obesa were commonly based on the description of non-type specimens determined by Costa Lima (1935) and Malogolowkin (1946), although their identities were doubtful. However, the recent redescription of R. obesa from the type-series from Texas, USA, confirmed a long period of misidentifications and a new species, R. cantareira Vilela & Bächli, was proposed based on Brazilian specimens. Thus, review of morphological and molecular traits of specimens previously identified as R. obesa in Neotropical biomes are necessary to check the identity and distribution of a group of sibling species: R. obesa, R. cantareira, R. gigantea (Thomson), R. pallida Hendel and R. pampeana Poppe et al. In the present paper, specimens previously determined as R. obesa, sampled in different Brazilian localities, were compared by morphological and molecular traits. Plates of female terminalia of R. cantareira and R. gigantea are presented for the first time. The spermathecal capsules (as well as the male epandrium) revealed useful characteristics to differentiate those species; these morphological differences were corroborated by a sequence fragment of COI. The specimens on which were based the descriptions of Rhinoleucophenga obesa sensu Costa Lima (1935) and sensu Malogolowkin (1946) were reviewed and confirmed as R. cantareira. Other Brazilian specimens from different localities, previously misidentified as R. obesa, were determined as R. gigantea or R. cantareira, with new records for both species. Therefore, the present study corresponds to the advance of identity definition and distribution of sibling species of Rhinoleucophenga commonly sampled in Neotropical inventory studies.